THE POSSIBLE PROTECTIVE EFFECTS OF OXYTOCIN ON CISPLATIN-INDUCED TOXICITY IN FEMALE RATS - Rahman, Zeinab; Hassan, Wedad; Garhy, Amany El (Acta Scientiae et Intellectus, 2024)
The present study aimed to assess the protective effect of oxytocin against cisplatin-induced liver, renal spleen and ovarian toxicities in female Sprague Dawly rats. Cisplatin (7.5 mg/kg, i.p. single dose) caused significant increase in blood urea, serum creatinine, liver enzymes: AST, ALT and alkaline phosphatase. Cisplatin caused decrease in catalase and reduced glutathione meanwhile it caused increase in the malondialdehyde content of kidney, liver and spleen homogenates. On the other hand, administration of oxytocin (800 μg/kg i.p) for six days with injection of a single dose of cisplatin onset of the day 3, ameliorated the cisplatin-induced nephrotoxicity and hepatotoxicity as indicated by the restoration of kidney, liver functions and oxidative stress biomarkers. Furthermore, oxytocin reduced the histopathological changes induced by cisplatin and caused decreased expression of caspase-3 in immunehistochemical studies of liver, kidney, spleen and ovarian tissues. In conclusion, oxytocin showed protective effects against cisplatin-induced toxicity in female rats due to its antioxidant and immunomodulatory functions.